Do increased doses to stem-cell niches during radiation therapy improve glioblastoma survival? - Adeberg, Sebastian; Harrabi, Semi B.; Bougatf, Nina; Bernhardt, Denise; Mohr, Angela; Hörner-Rieber, Juliane; Kölsche, Christian; Rieken, Stefan; Debus, Jürgen (Stem cells international, 2016)
Background and Purpose. The reasons for the inevitable glioblastoma recurrence are yet understood. However, recent data suggest that tumor cancer stem cells (CSCs) in the stem-cell niches, with self-renewing capacities, might be responsible for tumor initiation, propagation, and recurrence. We aimed to analyze the effect of higher radiation doses to the stem-cell niches on progression-free survival (PFS) and overall survival (OS) in glioblastoma patients. Materials and Methods. Sixty-five patients with primary glioblastoma treated with radiation therapy were included in this retrospective analysis. The SVZ and DG were segmented on treatment planning magnetic resonance imaging, and the dose distributions to the structures were calculated. The relationship of dosimetry data and survival was evaluated using the Cox regression analysis. Results. Conventionally fractionated patients () who received higher doses ( ≥ 40 Gy) to the IL SVZ showed improved PFS (8.5 versus 5.2 months; ). Furthermore, higher doses ( ≥ 30 Gy) to the CL SVZ were associated with increased PFS (10.1 versus 6.9 months; ). Conclusion. Moderate higher IL SVZ doses (≥40 Gy) and CL SVZ doses (≥30 Gy) are associated with improved PFS. Higher doses to the DG, the second stem-cell niche, did not influence the survival. Targeting the potential cancer stem cells in the SVZ might be a promising treatment approach for glioblastoma and should be addressed in a prospective randomized trial.
Gesehen am 11.08.2020